Uterine contractility in aged rats after administration of conditioned media from cryopreserved glial cell culture - Nesteruk, Hanna; Legach, Yevgeniy (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):300